Application of Happenstance Learning Theory (HLT) in new normal life after the COVID-19 pandemic - Fikri, Miftahul; Biran, Mega Iswari; Afdal, Afdal (Jurnal Aplikasi IPTEK Indonesia, 2023)
During the COVID-19 period many individuals were unable to work because of this outbreak. This research was conducted to apply Happenstance Learning Theory (HLT) during the new normal period. Happenstance Learning Theory is conducted with the aim of assessing skills in using coincidences in developing career opportunities. The method in this research is quantitative descriptive, the samples used in this study were 88 respondents using multistage random sampling techniques. The results of this study indicate that the skills in using opportunities are in the very low category with a percentage of 56%. And seen from the 5 dimensions of Happenstance Learning Theory namely Optimism is in the very low category 39.8%; Flexibility is in the low category of 31.8%; Persistence is in the very low category of 28%; Curiosity; in the medium category 30.7%, and Risk Taking in the very low category 26.4%. Based on the results of this study it was found that there is a need for careful career planning carried out by individuals in making career choices especially during the COVID-19 pandemic.